2017
DOI: 10.1016/j.ejpb.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased surface hydrophobicity via drug conjugation on the clearance of inhaled PEGylated polylysine dendrimers

Abstract: PEGylated polylysine dendrimers are attractive and well tolerated inhalable drug delivery platforms that have the potential to control the release, absorption kinetics and lung retention time of conjugated drugs. The clinical application of these systems though, would likely require partial substitution of surface PEG groups with drug molecules that are anticipated to alter their lung clearance kinetics and clearance pathways. In the current study, we therefore evaluated the impact of increased surface hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…While the authors revealed no significant changes in lung clearance as a result of acute lung inflammation, this study was limited to only 2 days. Our group has previously shown however, that nanomaterials are cleared from the lungs of rodents and sheep over a matter of weeks, not days [17][18][19]. The true impact of lung inflammation on the clearance kinetics of nanomaterials may therefore not be evident over short time periods.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…While the authors revealed no significant changes in lung clearance as a result of acute lung inflammation, this study was limited to only 2 days. Our group has previously shown however, that nanomaterials are cleared from the lungs of rodents and sheep over a matter of weeks, not days [17][18][19]. The true impact of lung inflammation on the clearance kinetics of nanomaterials may therefore not be evident over short time periods.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Rats were allowed to recover overnight from surgery prior to dosing the following day. Bleomycin was administered to rats (group 2) the day after rat, total faeces were collected over the entire sampling period and pooled to quantify the proportion of the 3 H dose excreted via the faeces using a previously described liquid scintillation assay [11,19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, dendrimers have excellent water solubility, as well as areas of increased hydrophobicity, allowing them to be very effective at carrying a drug payload [70]. Despite these advantages, dendrimer drug delivery is not a magic bullet, as it has a long production time and contradictory results [71,72,73]. While the unique chemical synthesis of dendrimers allows for more autonomy in design, few dendrimer designs vary from standards [70].…”
Section: Surface Modificationsmentioning
confidence: 99%